PENCITRAAN KRIYA SEBAGAI PRODUK SENI WISATA - Krishna Hutama (Universitas Trisakti, 2006)
AbstractNeed of souvenir to supply demand from local and international tourist could be assumed that keris was one of craft commodity with good prospect. The impact of tourism very influential to change over the shape of craft according to the tourist demands. Keris from center of Java souvenir that available for tourist was transmission media value that realized as an impression for tourist about everything they have got as long as their traveling. In the marketing contexts, imagination or creation of value impressed that tharnsfererd on souvenir was an important aspect to make tourism marketing succesfull. So that Central Java keris could be an associative bridge to recognize the culture which is the tourism placed AbstrakPengaruh pariwisata sangat menentukan terhadap prubahan bentuk bentuk karya seni sesuai dengan keinginan para wisatawan. Dalam konteks pemasaran, pencitraan atau penciptaaan kesan , kesan nilai yang diproyeksikan pada cenderamata merupakan faktor yang menentukan keberhasilan pemasaran pariwisata.Dengan demikian cenderamata produk kriya dapat menjadi jembatan yang bersifat asosiatif dalam mengenal budaya pariwisata setempat.Kajian penilitian ini menyimpulkan bahwa pergeseran nilai dan fungsi produk kriya cenderung disebabkan oleh adanya kebutuhan-kebutuhan baru sesuai dengan tuntutan perubahan jaman.